Parental Acceptance terhadap Anak dengan Disleksia dalam Film Wonderful Life - Amin, Barkatullah (INKLUSI, 2018)
This paper elaborates the acceptance process of a single parent who has a dyslexic child in the movie "Wonderful Life". The film showed a widower who has grown with her inspiring father. The value of life from her father influenced the way she educates her child. This research used a qualitative approach, inspired by Peirce semiotic and supported by the theory of five stages of grief. The paper concluded that, firstly, the parent’s acceptance of the dyslexic child gave a positive effect for herself and her child. Second, misperception in understanding the condition of the child has slackened the ability of the child. Third, the understanding of parent gave significant impact in choosing the appropriate education for her child. Fourth, that the depression happened to the mother was affected by not only child condition, but also the pressures from the family. [Makalah ini bertujuan melihat proses penerimaan orang tua atas kondisi anaknya yang memiliki disleksia dalam film Wonderful Life. Menggunakan pendekatan kualitatif dan didukung dengan teori the Five Stages of Grief, penelitian ini menunjukkan bahwa: Pertama, peneriman orang tua terhadap kondisi anaknya memberikan dampak positif bagi dirinya dan anaknya. Kedua, kesalahpahaman dalam memahami kondisi anak dapat menghambat kemampuan pada diri anak. Ketiga, pemahaman orang tua memberikan dampak signifikan dalam pengambilan keputusan pendidikan bagi anaknya, Keempat, depresi yang terjadi pada ibu tidak hanya diakibatkan oleh kondisi anaknya, tetapi juga tekanan dari keluarga.]